2017
DOI: 10.3748/wjg.v23.i22.4112
|View full text |Cite
|
Sign up to set email alerts
|

Can fecal microbiota transplantation cure irritable bowel syndrome?

Abstract: AIMTo verify the utility of treatment with fecal microbiota transplantation (FMT) in patients with irritable bowel syndrome (IBS).METHODSWe searched EMBASE, Cochrane Library and PubMed in March, 2017. The reviewed literature was based on two systematic searches in each of the databases. The MeSH terms used were IBS and fecal microbiota transplantation and the abbreviations IBS and FMT. Reference lists from the articles were reviewed to identify additional pertinent articles.RESULTSA total of six conference abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 36 publications
(85 reference statements)
1
39
0
1
Order By: Relevance
“…Frozen FMT suspensions were not inferior to fresh suspensions (59). A recent review combined data of case reports and studies treating IBS patients with FMT (60). When compiling all small uncontrolled studies, its authors found an overall improvement of symptoms in 58% of patients treated with FMT.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…Frozen FMT suspensions were not inferior to fresh suspensions (59). A recent review combined data of case reports and studies treating IBS patients with FMT (60). When compiling all small uncontrolled studies, its authors found an overall improvement of symptoms in 58% of patients treated with FMT.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…2,3 The view that an imbalance in the microbial community (dysbiosis) is an underlying cause of sickness provides a rationale for establishing commensal Koch's postulates for microbiota research 4 and raises hope that administering fecal microbiota transplants (FMTs) to eradicate a microbial imbalance could be developed as a cure. 5,6 The latter approach is successful in treating antibioticassociated colitis, 7 because here the FMT directly targets the underlying defect, namely an antibiotic-mediated disruption of the gut microbiota. 8 However, lasting benefits of FMT remain to be established for diseases associated with dysbiosis developing independently of antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Treatments aimed at altering gut microbiota such as antibiotics, probiotics, and case series of FMT have been described in IBS patients. Published case reports of FMT for treatment of IBS have shown improvement, but there is likely a publication bias, with negative reports not published . Additionally, since IBS is a heterogeneous disorder, the success of microbiota restoration in this population would be difficult to ascertain.…”
Section: Microbiota Replacement For Indications Other Than CDImentioning
confidence: 99%